Gambaran Pekerja Informal dan Faktor-Faktor yang Memengaruhinya di Indonesia Tahun 2022 - Sibagariang, Fahri Azis; Mauboy, Lourna Mariska; Erviana, Rissa; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2023)
This study aimed to determine an overview of informal workers in Indonesia and its determinants through specific analysis. The data used are data from The National Labor Force Survey and The National Socio-Economic Survey using quantitative research methods and descriptive and inferential analysis methods. The data analysis used was multiple linear regression analysis using the Ordinary Least Square (OLS) method using R studio. The results of this study indicate that there are more informal workers than formal workers. primary education completion rate and average hourly wages of workers have a significant negative impact to Informal workers percentage. In contrast, percentage of poor population influenced positively to informal workers percentage.